Chromosome identification for the carnivorous plant Genlisea margaretae - Tran, Trung D; Šimková, Hana; Schmidt, Renate; Doležel, Jaroslav; Schubert, Ingo; Fuchs, Jörg (Chromosoma, 2017)
Genlisea margaretae, subgenus Genlisea, section Recurvatae (184 Mbp/1C), belongs to a plant genus with a 25-fold genome size difference and an extreme genome plasticity. Its 19 chromosome pairs could be distinguished individually by an approach combining optimized probe pooling and consecutive rounds of multicolor fluorescence in situ hybridization (mcFISH) with bacterial artificial chromosomes (BACs) selected for repeat-free inserts. Fifty-one BACs were assigned to 18 chromosome pairs. They provide a tool for future assignment of genomic sequence contigs to distinct chromosomes as well as for identification of homeologous chromosome regions in other species of the carnivorous Lentibulariaceae family, and potentially of chromosome rearrangements, in cases where more than one BAC per chromosome pair was identified.
Keywords: BACs; Karyotyping; hybridizace in situ fluorescenční; Chromosomes, Plant; Multicolor fluorescence in situ hybridization (mcFISH); Magnoliopsida; In Situ Hybridization, Fluorescence; Genome Size; genom rostlinný; chromozomy rostlin; délka genomu; Reprobing; Genome, Plant; Genlisea